2022
DOI: 10.3390/nu14173476
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nutraceuticals in Elderly to Fight Inflammation and Immuno-Senescence: A Randomized Case-Control Study

Abstract: Elderly people are at high risk of suffering from infection and being affected by severe forms of disease because their immunosystem suffers from aging. The alteration of normal immune functions causes the increase of pro-inflammatory cytokines which can expose these people to increased risk of developing pathologies as cancer, diabetes, and/or arthritis. Some supplements could be helpful for restoring normal immune functions. We conducted a case-control study to evaluate the efficacy of a supplement containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The multilinear regression analyses showed that age is a positive prognostic factor, and this is in line with what has been observed in surgical studies focused on immune senescence [14]; the immune response tends to decrease with age, and TILs do the same.…”
Section: Discussionsupporting
confidence: 88%
“…The multilinear regression analyses showed that age is a positive prognostic factor, and this is in line with what has been observed in surgical studies focused on immune senescence [14]; the immune response tends to decrease with age, and TILs do the same.…”
Section: Discussionsupporting
confidence: 88%
“…We did not measure cholesterol or blood lipids in our study. A recent randomised case control study comparing the effects of a combined nutraceutical (including vitamins C, D and E) in young (18-50 years) and hospitalised older (> 65 years) participants found a significant reduction in circulating IL-6 and CRP levels in older participants following 12-week treatment [39]. Taken together, these findings support the contention that these combined nutraceutical supplements will be most effective in those either already not in robust health, or at risk of age-related diseases such as cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial aimed to test the possible effect of a nutraceutical supplement (comprehensive of Sambucus nigra, zinc, tyndallized Lactobacillus acidophilus (HA122), arabinogalactans, VitD, vitamin E, vitamin C, and group B vitamins) on some specific signatures of immunosenescence in hospitalized older adults. These supplements determined a reduction in inflammatory mediators such as IL-6, CRP, and lymphocyte number, and they were also associated with perceived better wellness [ 55 , 95 ]. Considering the effect of VitD on the immune system, mainly exerted through the inhibition of monocyte and cytokine overproduction and direct action on T lymphocytes, Rizka et al evaluated the potential effect of alphacalcidol supplementation in an inflammatory profile (Il-6, IL-10, TNF, CD4/CD8 ratio, CD8+, and CD28-) in 110 older fit or frail subjects.…”
Section: Vitamin D and Its Potential Impact On The Biological Hallmar...mentioning
confidence: 99%